A Literature Review on the Relationship between Iron and Zinc Levels in Diabetes Mellitus and the Effects of Their Supplementation - Sefti Atletika Asiani; Gaga Irawan Nugraha; Sunarjati Sudigdoadi (Budapest International Research and Critics University, 2021)
This study aims to review the relationship between iron and zinc in diabetes mellitus and the effects of iron and zinc supplementation on changes in blood glucose levels. The results showed that diabetes mellitus was associated with low zinc levels and high levels of iron in body serum, as well as low iron levels in diabetes mellitus with iron deficiency anemia. Zinc supplementation in diabetes mellitus and iron in diabetes mellitus with iron deficiency anemia can reduce levels of fasting blood glucose and hemoglobin A1c. Nutritional therapy with zinc and iron supplements can decrease blood glucose levels with results that are influenced by dosage and period of supplementation. Screening for iron deficiency anemia needs to be done in diagnosing diabetes mellitus and implementing nutritional therapy with biomarkers of blood sugar levels in serum.